Immigrant Arrival and Tuberculosis among Large Immigrant- and Refugee-Receiving Countries, 2005–2009. (23rd March 2017) - White, Zachary; Painter, John; Douglas, Paul; Abubakar, Ibrahim; Njoo, Howard; Archibald, Chris; Halverson, Jessica; Robson, John; Posey, Drew L.
Abstract : Objective . Tuberculosis control in foreign-born populations is a major public health concern for Australia, Canada, New Zealand, United Kingdom, and the United States, large immigrant- and refugee-receiving countries that comprise the Immigration and Refugee Health Working Group (IRHWG). Identifying and comparing immigration and distribution of foreign-born tuberculosis cases are important for developing targeted and collaborative interventions. Methods . Data stratified by year and country of birth from 2005 to 2009 were received from these five countries. Immigration totals, tuberculosis case totals, and multidrug-resistant tuberculosis (MDR TB) case totals from source countries were analyzed and compared to reveal similarities and differences for each member of the group. Results . Between 2005 and 2009, there were a combined 31, 785, 002 arrivals, 77, 905 tuberculosis cases, and 888 MDR TB cases notified at the federal level in the IRHWG countries. India, China, Vietnam, and the Philippines accounted for 41.4% of the total foreign-born tuberculosis cases and 42.7% of the foreign-born MDR tuberculosis cases to IRHWG. Interpretation . Collaborative efforts across a small number of countries have the potential to yield sizeable gains in tuberculosis control for these large immigrant- and refugee-receiving countries.